Determinants of willingness to pay for organic foods: evidence from a primary survey of conventional consumers - Islam, Shahidul (My University, 2018)
This study explores why conventional consumers choose to pay premium prices for organic foods. A structured interview was conducted with 750 randomly selected shoppers to collect consumers’ perception, purchasing decision and WTP for organic foods. Results suggest that the perception, purchase decision and WTP are highly related. Common attributes motivating consumers to pay higher prices are: organic foods are healthier, tastier, better quality and have more human touch than conventional foods. These variables are important as a group and not as an individual as these are linked in consumer’s perception, purchasing decision and WTP.
Keywords: organic foods; willingness to pay; consumer behavior